(3GdHOhQ GdRGgQI aj GdbQGAGJ GdYTQ GdeJhGJQIs - (3GdfTGQ , SQGL GdOjf CHh MaU YeQ Hf bGSe Hf eMeO GdeUQj GdCfUGQj, GdfTGQ,J (B900 (3g` s
(3ChdgG (B:s
(3hHYO aEf HYV CUObGFi habge Gddg JYGdi deG ojMH hjQVi SCdfj Cf CLeY cJGHkG aj GdbQGAGJ GdYTQ hCf CPcQ cd eSFdI ai eMdgG s
(3BNQgG (B:s
(3cGf QShd Gddg Udi Gddg Ydjg hSde jbhd YfO NJe GdbQBf Gddge GQMefj HGdbQBf hGLYdg dj EeGekG hfhQkG hgOi hQMeI Gddge PcQfj efg eG fSjJ Gfgi cdGe GHf GdLRQj s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B792s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B231s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI (B((3bQGAGJ (B1130) s
Keywords: (3GdbQGAGJ hGdJLhjOs